Reliability and optimal replacement interval of flexible hose assemblies in drinking water installations. (January 2020) - Błażejewski, Ryszard; Matz, Radosław; Nawrot, Tadeusz; Rudzik, Dariusz
Highlights: Theoretical and field query of 356 flexible hose assemblies for sanitary appliances. Reliability functions for cold and hot water hose assemblies. The optimal time period to replace stainless steel convoluted flexible hose assemblies. Abstract: The paper presents theoretical considerations and questionnaire examinations concerning reliability and replacement interval of flexible hose assemblies for washbasins, sinks and water closets. The topic is vitally important for providing home safety. The impact of operational temperature on durability of elastomeric tube was theoretically assessed. Questionnaire examinations covered 356 hoses installed in a block of flats in Poznan (Poland) and detached houses. The analyzed period of hoses' operation was 11 years or less in the case of earlier failure. During that time 41 hoses (approximately 12%) had failed. Reliability functions were obtained separately for cold and hot water installations. It was found that flexible hose assemblies for hot water were less reliable than those for cold water. The optimal time to replace hoses was estimated as 6–7 years.